2012
DOI: 10.1007/s00421-012-2522-6
|View full text |Cite
|
Sign up to set email alerts
|

Regional differences in facial skin blood flow responses to the cold pressor and static handgrip tests

Abstract: We have previously reported the unique regional responses of facial skin blood flow (SkBF) to oral application of the basic tastes without simultaneous systemic circulatory changes. In the present study, we determined whether a systemic circulatory challenge due to sympathetic activation induces regional differences in facial SkBF by observing the responses in facial SkBF and blood pressure to a 2-min cold pressor test (CPT) and static handgrip exercise (HG) by right hand in 20 healthy subjects. The CPT signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
3

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 20 publications
1
23
3
Order By: Relevance
“…Our finding of lower amplitude of blood pulsations in the nasal area of migraineurs suggests a stronger activation of the sympathetic vasoconstrictory nerves [28], [29]. However, in left-side migraineurs an increased parasympathetic activation in response to the pain has been suggested [19], supporting the link between autonomic imbalance and laterality of headache.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…Our finding of lower amplitude of blood pulsations in the nasal area of migraineurs suggests a stronger activation of the sympathetic vasoconstrictory nerves [28], [29]. However, in left-side migraineurs an increased parasympathetic activation in response to the pain has been suggested [19], supporting the link between autonomic imbalance and laterality of headache.…”
Section: Discussionmentioning
confidence: 46%
“…In addition to local changes in vascular reactivity, migraine has been proposed to be a manifestation of a systemic vasculopathy [36]. In addition, a relatively cold nose has been associated also with the emotions [29], and migraineurs are more sensitive to stress [37]. In summary, our data are consistent with the view [38] that migraine, especially migraine with aura, represents a final common phenotype of different pathogenic mechanisms including increased risk of stroke, right-to-left shunt, potential intravascular embolism, inherited vascular defects or autonomous dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Scalp blood flow is known to vary with a number of factors, including cardiac output, ambient temperature, blood 65%CO2 concentration and, most strongly, sympathetic nervous system (SNS) activity (Low et al, 1983, Khan et al, 1991, Drummond, 1991, Drummond, 1996, Drummond, 1997, Kashima et al, 2012). A degree of blood pressure autoregulation may occur, but much more weakly than in the cerebral vasculature (Wilson et al, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…Ipsilateral activation within the M1 during knee extensions has been observed before (Kashima et al, 2013), however, that ipsilateral activation was higher than contralateral activation was not expected. As it cannot be distinguished between exhibitory or inhibitory activation, the higher ipsilateral activation of the M1 might occur due to the inhibition of the non-involved (left) leg.…”
Section: Discussionmentioning
confidence: 61%
“…For instance, Christensen et al (2000) localized increased activity within the primary sensory (S1), primary motor (M1), and supplementary motor cortex during moderate pedaling exercise using PET. Different cortical activation patterns were observed comparing elbow and knee flexion/extension by fMRI (Kashima et al, 2013). Another fMRI study revealed increased activity within the left M1 and the dorsolateral premotor cortex (PMC) during repeated isometric knee extension and ankle plantar- and dorsiflexion (Newton et al, 2008).…”
Section: Introductionmentioning
confidence: 99%